A revision of the Neotropical genus Metasiphonella Duda, 1930 (Diptera: Chloropidae) - Riccardi, Paula Raile; Bazyar, Zeinab; Ismay, Barbara (Zootaxa, 2020)
The monotypic genus Metasiphonella, originally described from Costa Rica, is now formally recorded from South America with a new species from Brazil—M. amorimi sp. nov. The taxonomic revision includes a detailed description of adult external morphology, female and male terminalia, and the egg stage for all species. A lectotype of M. magnifica Duda is designated and new country records are given.